The use of social media by three political parties during South Africa’s 2014 general election - Samuel Umoh Uwem (Digital Policy Studies)
Since the first democratic election in South Africa in 1994, electoral campaigns have changed significantly, largely due to social media, which now play a vital role in influencing voters throughout the world. This study examines the social media campaigns of three major South African political parties, namely the African National Congress (ANC), the Democratic Alliance (DA) and the Economic Freedom Fighters (EFF), prior to the 2014 general election. Data comprised interviews with members of Parliament (MPs) of all three parties, and an analysis of their Facebook pages, Twitter feeds and YouTube channels. The study finds that, while all three parties made active use of social media, the full potential of this form of communication was not exploited, as they continued to disseminate traditional political messages instead of interacting actively with voters.